2002
DOI: 10.1016/s0736-0266(01)00160-7
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic compression modulate matrix metabolism in tissue engineered cartilage

Abstract: Static and dynamic compression are known to modulate the metabolism of articular cartilage. The present study focused on determining the effects of compressive loading on the metabolism of sulfated glycosaminoglycans (S-GAG) and protein in tissue engineered cartilage constructs. Cartilage constructs were subjected to static or dynamic compression for 24 h and radiolabeled with %04 and 'H-proline to assess the total synthesis and percentage retention of S-GAG and total protein, respectively. Static compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(145 citation statements)
references
References 33 publications
0
140
2
2
Order By: Relevance
“…It is difficult to assess the individual effects of each of these potential stimuli due to the differences between experiments; however some trends do emerge from the data. Continuous loads or high frequency, high magnitude loads inhibits cell processes such as matrix synthesis and growth (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Sironen et al, 2002;Wu and Chen, 2000), while low magnitude dynamic loading stimulates matrix synthesis (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Wu and Chen, 2000). Reduced chondrocyte proliferation was also recorded in DMB immobilised chick growth plates (Germiller and Goldstein, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assess the individual effects of each of these potential stimuli due to the differences between experiments; however some trends do emerge from the data. Continuous loads or high frequency, high magnitude loads inhibits cell processes such as matrix synthesis and growth (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Sironen et al, 2002;Wu and Chen, 2000), while low magnitude dynamic loading stimulates matrix synthesis (Buschmann et al, 1995;Davisson et al, 2002;Fukuda et al, 1997;Wu and Chen, 2000). Reduced chondrocyte proliferation was also recorded in DMB immobilised chick growth plates (Germiller and Goldstein, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that mechanical loading, applied using a variety of devices [201] has been included as a key element in cartilage TE strategies, in order to enhance cell differentiation and/or tissue development in vitro. Indeed, a number of studies have reported stimulated chondrocyte metabolism and/or enhanced cartilage matrix production in response to dynamic loading, although these responses were greatly dependent upon the specific magnitude and/or frequency applied [105,[202][203][204][205][206][207]. Despite these numerous proofs of principle that mechanical conditioning can upregulate gene expression and tissue development, little is currently known about which specific mechanical forces, or regimes of application (i.e.…”
Section: Bioreactors To Establish and Maintain 3d Culturesmentioning
confidence: 99%
“…These applied dynamic culturing conditions (perfusion/fluid flow, hydrostatic pressure or dynamic compressive loading) enhance developing neo-tissues F o r P e e r R e v i e w 4 through enhanced nutrient delivery and metabolic waste removal (15)(16)(17) and/or by providing a mechanical stimulus to the cells (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). For example, Akmal et.…”
Section: Introductionmentioning
confidence: 99%